Analysis of Hypnotherapy Method in Changing Fighting Behavior of Children Playing at SDN Jango Elementary School, Central Lombok Regency - Raodatul Jannah; Muhamad Zaenal Asikin (Syntax Corporation Indonesia, 2024)
According to WHO in Indonesia there are 8-10% of children with special needs. Children with special needs have a lower level of health in play than normal children. Based on a survey in Velezuelan and a study in Malaysia, autistic children have calculus with poor criteria. Autism is one of the complex disorders of child development. Autistic children have problems with their behavior, one of which is hyperactivity or hyperactivity. Hypnotherapy is a method of treatment and healing commonly known as hypnosis. Hypnosis is one therapy that is expected to reduce the level of hyperactivity and cooperation in children playing around their environment at school. This study aims to analyze the Hypnotherapy Method in Changing the Fighting Behavior of Children Playing in SDN Jango Elementary School, Central Lombok Regency. This study used descriptive qualitative method. As a result, although hypnotherapy can be an effective tool in improving one's mental well-being, it is important to consider individual needs and preferences as well as consult a qualified professional before using this method.